MODERATING EFFECT OF AUDIT QUALITY ON VALUE RELEVANCE OF FAIR VALUE MEASUREMENTS HIERARCHY OF LISTED FINANCIAL SERVICES COMPANIES - Tesleem Olayinka Adeyemi (Gusau Journal of Accounting and Finance, 2024)
The International Financial Reporting Standards (IFRS) was developed to enhance transparency and high-quality information as a principle-based standard that allows some degree of flexibility in financial reporting process. An important feature of IFRS is that of paradigm shift from historical cost to fair value-based measurement of certain assets and liabilities. Consequently, the reliability of fair value measurement became a subject of concern, particularly in most developing economies with inactive market for financial instruments. The study examines the value relevance of fair value measurement hierarchy for financial instruments taking into consideration the moderating role of audit quality. The sample comprised of thirty-six (36) out of fifty-nine (59) financial services companies listed on the Nigerian Exchange Group as at 31st December, 2018. The study employed OLS multiple regression and heteroskedasticity corrected standard errors were used to test the relationship. The study revealed fair value measurements hierarchy is value relevant as it has significant impact on share prices. Specifically, Level 1 and Level 2 fair value financial assets were found to have positive significant influence on the share price of listed financial services companies in Nigeria while Level 3 fair value financial assets were found to be negatively and insignificantly influencing the share prices. Lastly, audit quality was found to be positively and significantly influencing the value relevance of fair value financial assets of listed financial services companies in Nigeria. The study recommends among others, the need for regulatory authorities to create an active market for financial instruments to fully achieve the fundamental objective of fair value and to limit the uncertainty and ambiguities around the application of level 3 fair value hierarchy. Also, investors should plan and allocate their investments to companies with lower information risk (i.e companies with lower level 3 fair value estimates) in making appropriate investment decisions relating to financial instruments such as stocks, bonds, and fixed interest deposit.